The trend of academic achievement among the Malaysian boys and girls: where are the boys? - Ahmad, Nor Aniza; Hassan, Siti Aishah; Ahmad, Abdul Razak; Chua, Lay Nee; Othman, Nor Hashim (Global Academy of Training and Research, 2017)
Objective – Gender differences in education remain as one of the global issues that has been widely and comprehensively discussed. This study aims at exploring the pattern of academic achievement of boys and girls in Malaysia. Methodology/Technique – The study analyzes the data of student achievement in public examination from 2008 until 2014, which were obtained from the Malaysian Examination Board. Findings – The findings showed that Malaysian girls performed better than Malaysian boys. The findings also showed that there were significant differences in academic achievement between the boys and the girls. Novelty – This study implicated the need to identify the factors causing the achievement gap across genders. Hence, strategies and interventions can be undertaken to reduce the gap.